Triple careers of athletes: exploring the challenges of planning a pregnancy among female elite athletes using semi-structured interviews - Dietz, P.; Legat, L.; Sattler, M.; Poppel, M. (BMC Pregnancy and Childbirth, 2022)
Abstract: Background: The challenging factors that elite athletes perceive for combining their sportive career with planning a pregnancy and motherhood need to be identified in order to develop supportive measures. Therefore, this study aimed to explore challenges associated with planning a pregnancy among female, non-pregnant elite athletes. Methods: Semi-structured skype-interviews were performed among female elite athletes (athletes competing on national or international level) aged 28 years or older. Using Mayring`s qualitative content analysis approach, anchor examples served to identify potential challenges of planning a pregnancy which were categorized independently by two researchers.Results: Interviews of 16 elite athletes (mean age 30.7 years) entered analysis. Eleven challenges of planning a pregnancy were identified, categorized into organizational / environmental, financial, personal, and physical factors.Conclusions: With regard to financial challenges, we propose mandatory maternity leave and continuation of the contracts and salary. Furthermore, mentoring programs may help to provide support and advice to new generations of female elite athletes and help to reduce concerns regarding the wish of becoming pregnant during a sportive career. In order to reduce physical concerns regarding pregnancy and exercise, we see a need for scientific studies investigating the association of sport discipline specific characteristics on sportive performance and the mother´s, fetus` and child´s health. Finally, the results of the current study may be used in future quantitative studies to test specific hypotheses.